A comparative-study between visible-light-activated and autopolymerizing sealants in relation to retention - Gandini, M.; Vertuan, Valdemar [UNESP]; Davis, J. M. (Amer Soc Dentistry Child, 1991)
Two hundred twenty-nine first permanent molar occlusal surfaces were treated with sealants, from a group of sixty-one children. When the three sealants were analyzed at the end of the six-, twelve-, eighteen-, and twenty-four-month periods, it was observed that retentive loss was gradual. Both Concise and Delton showed superior retention when compared with Sealite.